(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The aim of this study was to define a relationship between heavy metal (Cu, Mo) pollution of soil and various extracellular enzyme activities. Six enzymatic activities involved in cycles of carbon, nitrogen, phosphorus and sulfur (β-glucosidase, chitinase, leucine-aminopeptidase, acid phosphomonoesterase, alkaline phosphomonoesterase, and arylsulphatase) as well as microbial biomass were determined in soil samples collected in the surroundings of Zangezur Copper and Molybdenum Combine. The investigations showed that pollution of soil with copper and molybdenum led to a decrease in microbial biomass and soil enzymatic activity, which in turn had a negative impact on cycles of chemical elements, in particular C, P, N and S. This gives reason to conclude that the changes in soil microbial biomass and enzymatic activity may act as indicators of soil biological activity and quality.